2004
DOI: 10.1007/s00392-004-0094-0
|View full text |Cite
|
Sign up to set email alerts
|

Propranolol inhibits IK(Ado) by competetive A1-receptor interaction

Abstract: Propranolol inhibits IK(Ado). Inhibition is not due to beta-receptor blockade. Predominantly an interaction with A1-receptors seems to be involved. The observations in part might explain the anti-arrhythmic properties of the drug in ischemic/fibrillating myocardium based on the prolongation of refractoriness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…Results from a representative experiment are shown in Figure 6A. The IC 50 s of compounds tested were in good correlation with data obtained by other types of assays [9][10][11][12][13][14][15][16] (Table 1). For example, IC 50 s for isoproterenol 10 and verapamil 13 tested in other models were 13 nM (isolated rabbit cardiomyocytes) and 167 nM (isolated guinea pig hearts), respectively.…”
Section: Assessment Of Positive and Negative Chronotrope Effectssupporting
confidence: 80%
“…Results from a representative experiment are shown in Figure 6A. The IC 50 s of compounds tested were in good correlation with data obtained by other types of assays [9][10][11][12][13][14][15][16] (Table 1). For example, IC 50 s for isoproterenol 10 and verapamil 13 tested in other models were 13 nM (isolated rabbit cardiomyocytes) and 167 nM (isolated guinea pig hearts), respectively.…”
Section: Assessment Of Positive and Negative Chronotrope Effectssupporting
confidence: 80%
“…On the other hand, beta adrenergic receptors bind to the same stimulatory G-proteins [31,32]. Therefore, theoretically it can be judged that inhibitors of such receptors may decrease activation of the corresponding G-proteins, which eventually lead to decreased cellular concentration of cAMP and reduced response to dipyridamole infusion [17,26,33]. Based on these facts, others concluded that “much of the coronary vasodilation associated with hypoxia is dependent on adrenergic activation and that adenosine may only play a role in sustained hypoxic vasodilation when adrenergic receptors are intact” [33].…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies suggest that acute beta-blocker administration may reduce the presence and severity of myocardial perfusion defects with dipyridamole stress [8-17]. Nevertheless, most of such studies have been performed with short-term or acute beta-blocker treatment, some after intravenous administration, rather than after long-term oral beta-blocker treatment so that their methods differ from the usual clinical scenario encountered in many patients referring for dipyridamole myocardial perfusion imaging (DMPI) [8-17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation